The asymmetry of democratization – the case of the Balkan states - Bujwid-Kurek, Ewa (Balcanica Posnaniensia. Acta et studia, 2025)
The primary objective of this study is to address the question of whether, in the Balkan states, democratization – conceived as the political system transformation-displays characteristics of symmetry or whether it currently reveals signs of asymmetry. The political systems of Albania, Bosnia and Herzegovina, Kosovo, North Macedonia, and Serbia were subjected to analysis. All the countries analyzed experience, to varying degress, deviations from the established trajectory of each country, the asymmetry of democratization is evident. Serbia is most notably affected, as it consistently ranks lowest across nearly all examined dimensions (freedom, democracy evolution, democracy index, situational assessment of democracy, media freedom, and perceptions of corruption), with a clear downward trend in these indicators. Bosnia i Herzegovina, as well as North Macedonia, follow in the rankings. In contrast, Albania and, surprisingly, Kosovo, achieve relatively the best results. Particulary concerning is the perception of corruption, especially in the case of North Macedonia.